Amnesia for loss of consciousness is common in vasovagal syncope. - Kenny, Rose; Langan, Yvonne (My University, 2011)
The aim of this study was to determine the prevalence of amnesia for loss of consciousness (A-LOC) in those who have a history suggestive of vasovagal syncope (VVS) and who develop syncope on head-up tilt (HUT) table testing. Furthermore, we wished to determine if A-LOC is an age-dependent phenomenon in VVS and whether haemodynamic parameters on tilting can predict for A-LOC. Methods and results: Patients were recruited in a dedicated syncope unit and underwent neurocardiovascular evaluation as indicated under European Society of Cardiology guidelines to illicit a diagnosis of VVS. A set protocol of questioning occurred following induced syncope to determine the presence of A-LOC. The prevalence of A-LOC following syncope on tilting was 28% (44/159). Forty-two per cent of those ≥60 years of age vs. 20% <60 years of age experienced amnesia post-induced syncope (P=0.003). However, regression analysis did not show age to be an independent predictor for A-LOC. Blood pressure change between those without amnesia and those with amnesia showed no significant difference (P=0.687). There was a significant difference in heart rate response; those experiencing amnesia had reduced bradycardic response on HUT compared with those without amnesia (P=0.001). Conclusion: Amnesia for loss of consciousness is common in VVS. Although more prevalent, it is not unique to older age-groups. Absence of syncope associated bradycardia during HUT testing predicts for A-LOC.
PUBLISHED
Keywords: Amnesia; Vasovagal scope; Head-up tilt Table test; Unexplained falls; Ageing; Neuroscience